Subcutaneous versus Sublingual Allergen Immunotherapy in Allergic Rhinitis and Asthma: A Comparative Narrative Review - Pietrucha, Tomasz; Gołdyn, Mikołaj; Kubala, Karolina; Grabińska, Magdalena; Halik, Paulina; Jusiak, Justyna (Quality in Sport, 2026)
Allergen-specific immunotherapy (AIT) represents the only disease-modifying intervention for IgE-mediated allergic diseases, including allergic rhinitis and allergic asthma. Among the currently available administration routes, subcutaneous immunotherapy (SCIT) and sublingual immunotherapy (SLIT) are the most extensively studied and clinically implemented. Despite their widespread use, uncertainty persists regarding their relative efficacy, safety, and real-world applicability across different patient populations and allergen types. AIM: The aim of this study was to critically compare the clinical effectiveness, safety profile, and treatment adherence of SCIT and SLIT based on data derived from PubMed-indexed randomized controlled trials, systematic reviews, and meta-analyses. Material and methods: A narrative synthesis of peer-reviewed literature was conducted, focusing on studies directly or indirectly comparing SCIT and SLIT in patients with allergic rhinitis, allergic asthma, or rhinoconjunctivitis. Primary endpoints included symptom score reduction and medication use, while secondary outcomes encompassed adverse events, immunological responses, and adherence rates. Results: Both SCIT and SLIT demonstrated significant clinical efficacy compared with placebo or pharmacotherapy alone. Overall symptom reduction and medication sparing effects were largely comparable between the two modalities. SCIT showed a trend toward slightly greater efficacy in selected allergens, particularly grass pollen, whereas SLIT consistently exhibited a superior safety profile with fewer systemic adverse reactions. Conclusion: SCIT and SLIT are both effective forms of allergen immunotherapy. While SCIT may provide marginal advantages in symptom control in specific clinical contexts, SLIT offers improved safety and convenience. Treatment choice should therefore be individualized, considering patient characteristics, allergen profile, and risk tolerance.